Keseimbangan Karakter Feminin dan Maskulin Dalam Mewujudkan Masyarakat Madani - Ina Salmah Febriani (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2021)
Culture and people are two things that cannot be separated. The existence of culture because it is related to the existence of humans in a place who do activities together from generation to generation to be an entrenched habit. Society as an important element culture has role to create a civil society (ethical and civilized society). Men and women as 'containers' of culture have the same responsibility in shaping civil society. However, the reality in society is different. Social inequality is still common. Inequality and discrimination based on sex still exist, including various women's problems that occur related to impoverishment, discrimination and violence against women in almost all industrial sectors. Impoverishment is reflected in the absence of spouse allowances for female workers, low wages, and no overtime pay. The type of research is descriptive research that will present a description of the two characters that each individual naturally possesses. This research will prove that humans are equipped with two characters (given) from God— feminine and masculine. If these two characters can be balanced optimally, all forms of discrimination will be able to be avoided so that each individual can work together in harmony to create a civil society.